An open label, multicenter clinical trial that investigated the efficacy and safety of leuprorelin treatment of central precocious puberty in Chinese children. Issue 51 (23rd December 2021) - Luo, Xiaoping; Hou, Ling; Zhong, Yan; You, Cheng; Yang, Yu; Wu, Xian; Li, Pin; Zhou, Shasha; Qiu, Wenjuan; Zhang, Huiwen; Liu, Ying; Qian, Ye; et al.
Abstract: Background: Leuprorelin is an analog of gonadotropin-releasing hormone that is used for the therapy of central precocious puberty (CPP). The aims of this prospective, open label, multicenter clinical trial were to establish its efficacy and safety during long-term use. Methods: Patients, who were all children, were treated with 1.88 to 3.75 mg leuprorelin subcutaneously once every 4 weeks for a total of 96 weeks between 2015 and 2018. The primary endpoint was the rate of occurrence of adverse events (AEs) and the secondary endpoint was no progression in the Tanner stage or regression by week 96 compared to baseline. Results: A total of 307 CPP patients, 305 (99.3%) females and 2 males (0.7%), completed the 96-weeks of treatment. Due to limited data for male patients, they are not discussed in the efficacy results. Treatment-emergent AEs (TEAEs) were reported for 252 (82.1%) patients, mostly (79.5%) being mild or moderate and only 33 (10.7%) of patients experienced TEAEs related to leuprorelin therapy. The most frequent (>2%) drug-related TEAEs were injection site induration (4.6%, 14/307) and vaginal bleeding (2.3%, 7/305). After treatment, 83.5% of patients had regression or no progression in the Tanner stage (95% confidence interval: 78.68%, 87.62%) and the majority had decreased gonadotropin-releasing hormone-stimulated peak luteinizing hormone and follicle-stimulating hormone concentrations, as well as reduced sex hormone concentrations and a reduction in the bone age/chronological age ratio compared to baseline. Conclusions: The trial revealed that CPP was effectively treated in most patients who received leuprorelin for nearly 2 years. Any drug-related AEs were reported with low incidence (<5%) and were consistent with the known safety profile of leuprorelin. Trial registration: The trial was registered at ClinicalTrials.gov (registration number: NCT02427958).